Penerapan Online Performance Assessment guna Mengukur Kemampuan Argumentasi Ilmiah Peserta Didik Materi Fluida Dinamis (IPF: Inovasi Pendidikan Fisika, 2022)
Abstract This research aims to measure the level of students' ability to argue scientifically using Performance Assessment. Performance Assessment is a form that can make students understand, master skills and are competent in observing or providing results. In this study, the assessment used is Performance Assessment, which is to assess the ability of scientific argumentation with components (claims, data, warrants, backings, and qualifiers) of students. This research uses a quantitative survey method, with one data being a test and two data being a questionnaire. The sample selection used random sampling so that the respondents obtained as many as 36 students in SMA Negeri 14 Surabaya. Based on the results of the data obtained, there is a positive and significant influence. Instruments on Performance Assessment affect the ability of scientific argumentation of students in learning Physics by getting a high/good category. And from the results of the response questionnaire, there is a positive relationship, namely that students are well interested in the application of Performance Assessment and learning is carried out using scientific arguments. Keywords: Performance Assessment, Scientific argumentation, Dynamic fluid